Semisimple groups interpretable in various valued fields - Yatir Halevi; Assaf Hasson; Ya'acov Peterzil (Forum of Mathematics, Sigma)
We study infinite groups interpretable in power bounded T-convex, V-minimal or p-adically closed fields. We show that if G is an interpretable definably semisimple group (i.e., has no definable infinite normal abelian subgroups) then, up to a finite index subgroup, it is definably isogenous to a group